2007
DOI: 10.1373/clinchem.2006.075085
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Markers within —SEA Breakpoints for Prenatal Diagnosis of HbBarts Hydrops Fetalis

Abstract: Background:We sought to develop a rapid prenatal diagnostic test for simultaneous detection of HbBarts hydrops fetalis and exclusion of maternal contamination. Methods: We developed a multiplex quantitative fluorescent PCR (QF-PCR) test that detects the presence/ absence of 2 microsatellite markers (16PTEL05/16PTEL06) located within breakpoints of the Southeast Asia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Our results showed that indirect testing based on fluorescent multiplex PCR can be safely used for NIPD, reaching sensitivity and specificity similar to those seen in previous studies [10,21,23,24]. However, this test is less informative than the SNP-haplotype-based approach by next-generation sequencing [25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that indirect testing based on fluorescent multiplex PCR can be safely used for NIPD, reaching sensitivity and specificity similar to those seen in previous studies [10,21,23,24]. However, this test is less informative than the SNP-haplotype-based approach by next-generation sequencing [25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 86%
“…The objective of noninvasive prenatal diagnosis in at-risk patients with double-gene deletions is to avoid invasive testing where the foetus is likely to be normal or heterozygote. We have previously described highly polymorphic microsatellite markers located within the deleted regions of SEA, THAI and FIL (Ho et al, 2007). We hypothesized that in cases where the foetus inherits the normal paternal allele, the undeleted paternally inherited fetal allele can be detected in the maternal plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other sophisticated methods using fluorescence-based PCR amplification of microsatellite markers [33], this combined PCR assay requires neither additional equipment nor additional complexity. The procedure is cheaper, more practical and directly applicable in most PCR laboratories, possibly facilitating a prevention/control program for this severe thalassemia in the region.…”
Section: Discussionmentioning
confidence: 99%